Creating a new normal for AFM services: 3D laser scanning to BIM for LCC application on built asset - Hazumi, Hazman; Ayob, Mohd Fairullazi; Md. Sharif, Harlina (2018)
Application of 3D laser scanning or Scan to Building Information Modelling (Scan-to-BIM) refers to the process of 3D laser scanning of a physical object that creates an accurate digital representation of the object. The representation of the object can then be used for planning, designing, assessing progress and evaluating possibilities in creating a new normal in AFM services industries.